Effect of Exposure Pili Protein 65.5 kDa Klebsiella pneumoniae on Interferon Gamma Levels - Dini Agustina; Bella Jiwangga; Yudha Nurdian; Enny Suswati; Diana Chusna Mufida; Mohammad Ali Shodikin (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Klebsiella pneumoniae is a Gram-negative bacterium that is mostly found as a nosocomial disease in hospitals. This bacterium is the largest contributor to the number of causes of pneumonia. Immune responses that play a role against K. pneumoniae is interferon-gamma (IFN-γ) as cellular immune responses, which function on the mucosal barrier in response to infection and contribute to the initial defense against various pathogens. The purpose of this study was to determine the effect of exposure to K. pneumoniae pili protein 65.5 kDa on IFN levels in mice. Methods: Thirty BALB/C mice were divided into three groups: K1 given phosphate buffer saline, K2 given pili protein and Freund's adjuvant, and K3 given Freund's adjuvant. The measurement of IFN-γ levels was carried out by enzyme-linked immunosorbent assay, the results of which were analyzed using the Kruskal-Wallis. Results: Pili protein 65.5 kDa K. pneumoniae showed a positive hemagglutination test with the highest titer of 1/8, which was indicated by the absence of red aggregate dots at the bottom of the well. Analysis test showed that the highest concentration of IFN-γ levels was in the control group and the lowest IFN-γ level was found in the adjuvant group. Conclusion: Pili protein 65.5 kDa K. pneumoniae had a role as a hemagglutinin protein and there was no effect of K. pneumoniae pili protein 65.5 kDa on IFN-γ levels in mice.